1998
DOI: 10.1002/(sici)1098-2736(199804)35:4<463::aid-tea16>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on being female in school science: Toward a praxis of teaching science

Abstract: This essay interrogates the phenomenon and the implications of being female in school science through girls' and young women's stories interwoven with my own narrative as a woman teacher/researcher in science education. The intent is to raise awareness of issues related to being female in conventional science teaching, and to suggest some alternative perspectives and approaches for action and reflection. I discuss several directions within my teaching which announce my own interpretation of bell hook's "engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 1 publication
0
16
0
1
Order By: Relevance
“…Drawing upon such resources, new ones could be developed exemplifying a wider variety of scientific concepts and used in a wider variety of settings. In addition to identifying existing narratives that could be used in science, it might also be useful to explore the idea of students constructing their own oral or written narratives as way of engaging with and making meaning of natural phenomena and communicating scientific ideas as described in other studies (e.g., Conle, 2003;Meyer's 1998).…”
Section: Implications For Theory Practice and Researchmentioning
confidence: 84%
See 2 more Smart Citations
“…Drawing upon such resources, new ones could be developed exemplifying a wider variety of scientific concepts and used in a wider variety of settings. In addition to identifying existing narratives that could be used in science, it might also be useful to explore the idea of students constructing their own oral or written narratives as way of engaging with and making meaning of natural phenomena and communicating scientific ideas as described in other studies (e.g., Conle, 2003;Meyer's 1998).…”
Section: Implications For Theory Practice and Researchmentioning
confidence: 84%
“…A major feature of such genres is the excision of the personal. Meyer (1998) argues that within the science learning context are situated constructions of meaning that are dependent upon the surrounding discourse, however, there are a number of obstacles to scientific discourse such as "its formal nature, the vernacular is unheard of, and comfortable patois has no place" (p. 467)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is evident when looking more closely at studies done by Klawe and Leverson (1995), Meyer (1998), as well as Ceci, Williams, and Barnett (2009). Klawe and Leverson (1995) followed 2,000 high school graduates in Michigan.…”
Section: Introductionmentioning
confidence: 56%
“…This is disquieting information as both groups of male and female students were highly qualified to do well in a science major. Additionally, Meyer (1998) found that females who had both high verbal and math scores on SATs were less likely than male students to pursue a science major in their higher education career. Likewise, Ceci, Williams, and Barnett (2009) found that females who had both high math and verbal scores were still more likely to not enter a math intensive field, such as, education or health, than male students with the same abilities.…”
Section: Introductionmentioning
confidence: 99%